1997
DOI: 10.1046/j.1471-4159.1997.68041542.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Two Types of Secretory Vesicles in the Human Neuroblastoma SH‐SY5Y

Abstract: Western blot analysis showed that the human neuroblastoma SH-SY5Y expresses the proteins synaptotagmin I, synaptobrevin, synapsin I, rab3a, syntaxin, SNAP-25, NSF, a-SNAP, and munc-1 8, which have been implicated in the movement, docking, and fusion of vesides during exocytosis from other neuroendocrine cells. The subcellular localization of secretogranins land II, synaptotagmin I, neuropeptide Y, rab3a, synaptobrevin, synaptophysin, and syntaxin was investigated by immunofluorescence microscopy and revealed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 28 publications
1
34
0
Order By: Relevance
“…Neurites and their boutons responded to receptor activation ( Fig. 1e) and have been proposed to provide release sites [39,40]. We therefore probed the effect of A 2A -receptor activation on noradrenaline release.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurites and their boutons responded to receptor activation ( Fig. 1e) and have been proposed to provide release sites [39,40]. We therefore probed the effect of A 2A -receptor activation on noradrenaline release.…”
Section: Resultsmentioning
confidence: 99%
“…1b). Probably, release sites are present on SH-cell neurites, which were found to be rich in vesicles and proteins of the vesicle-fusion apparatus [39,40]. Thus, A 2A -receptors may be located close to release sites and, in addition, they meet the criteria for docking to the 'presynaptic' active zone.…”
Section: Discussionmentioning
confidence: 99%
“…In SH-SY5Y cells, it has been suggested that two types of secretory vesicles exist, small synaptic-like vesicles (SSLVs) and the large dense core vesicles (LDCVs) (Goodall et al, 1997). LDCVs can be followed with a specific marker, secretogranin II, and distinguished from lighter SSLVs with synaptophysin, which is present only in light vesicles.…”
Section: Intravesicular Localization Of ␣-Synmentioning
confidence: 99%
“…For these studies, we used human neuroblastoma SH-SY5Y cells, a well characterized dopaminergic cell line that expresses endogenous syntaxin 1 and exhibits SNARE-mediated neurotransmitter release (54,55). Overexpression of Staring in SH-SY5Y cells significantly enhanced the ubiquitination of endogenous syntaxin 1, as indicated by the appearance of a high molecular weight smear containing Myc-ubiquitin-modified syntaxin 1 (Fig.…”
Section: Figmentioning
confidence: 99%